Impact of Digital Contexts in the Training of University Education Students - Violeta Cebrián-Robles; Francisco José Ruíz-Rey; Manuela Raposo-Rivas; Manuel Cebrián- (MDPI AG, 2023)
The Internet is an important source of information and is a real ecosystem for learning that has provided important advances in education, although it has also generated problems, especially in terms of data security, identity theft, and cyber-plagiarism. During the COVID-19 pandemic, we had the opportunity to check levels of development in terms of infrastructures and digital competence, and subsequently detected serious problems in online assessment. In particular, the behaviour and digital competence of future teachers are essential, as they will inevitably be role models for their students. The present study analyses academic cyber-plagiarism derived from digital ecosystems during the pandemic in the academic work of pre-service teachers, advancing studies and warnings regarding Artificial Intelligence as a new learning ecosystem. A validated online questionnaire is used that considers the digital context surrounding training both during and after the pandemic. For the factor analysis, both descriptive and correlational, 324 responses from three Spanish universities are analysed. The confirmatory factor analysis reports four factors: the digital context of the pandemic as an opportunity for plagiarism, the response of the educational community to plagiarism, and both the unconscious and intentional misuse of sources. It is concluded that the digital context of the pandemic provided an opportunity for academic plagiarism, conscious or unconscious, with a clear distinction according to gender and the degree of reference. Finally, it is recommended to promote students' digital skills to avoid risks such as cyber-plagiarism or authorship theft, using institutional repositories that can provide students with prominence by safely and ethically publishing their intellectual creations. Similarly, national policies are required to address advances in AI in education.